GEOGRAPHIC TONGUE WITH BURNING MOUTH SYNDROME (CASE REPORT) - Sari, Nendika Dyah Ayu Murika; Mujayanto, Rochman (Odonto : Dental Journal, 2021)
ABSTRACTBackground: Geographic tongue is a condition that involves the dorsal surface of the tongue. This condition is usually painless, but in some cases, it may be accompanied by a burning sensation.The cause is unknown, but it is thought to be related to heredity, hormonal imbalances, allergies, and anemia. The aim of this study is to describe the geographic tongue, which is associated with burning mouth syndrome. Procedure: A 23-year-old woman came to RSIGM Sultan Agung Semarang with the chief complaint of fissure front tongue and moving spots, which made her sore when eating spicy food. According to the findings of the investigations, the MCV and MCH values were low, while the total IgE level was higher than normal. Geographic tongue with burning mouth syndrome et causa allergy and iron deficiency were the diagnoses in this case. The treatment for this condition is iron containing vitamins. Conclusion: More investigation is required to determine the correct diagnosis, etiology, and treatment. Iron supplements can support to reduce the complaints. As a follow-up management of allergic conditions and iron deficiency, some more examinations by dermatologist and internist are required.